2005
DOI: 10.1117/12.601061
|View full text |Cite
|
Sign up to set email alerts
|

<title>Effective design strategy for a magneto-rheological damper using a nonlinear flow model</title>

Abstract: This paper presents an effective design strategy for a magnetorheological (MR) damper using a nonlinear flow model. The MR valve inside a flow mode MR damper is approximated by a rectangular duct and its governing equation of motion is derived based on a nonlinear flow model to describe a laminar or turbulent flow behavior. Useful nondimensional variables such as, Bingham number, Reynolds number, and dynamic (controllable) range are theoretically constructed on the basis of the nonlinear model, so as to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 17 publications
0
27
0
Order By: Relevance
“…However, at a speed of 6.6 m/s (260 in/s), the dynamic range reduced nominally to D ≈1. They hypothesized that the transition from controllable ( D > 1) to uncontrollable behavior ( D ≈1) is related to the transition of fluid flow from laminar to turbulent, which is supported by the analysis of Mao et al (2005). Browne et al (2009) conducted impact tests of an MREA at stroking velocities ranging from 1.0 to 10 m/s and showed that the MR damper force could be tuned by adjusting the magnetic field.…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…However, at a speed of 6.6 m/s (260 in/s), the dynamic range reduced nominally to D ≈1. They hypothesized that the transition from controllable ( D > 1) to uncontrollable behavior ( D ≈1) is related to the transition of fluid flow from laminar to turbulent, which is supported by the analysis of Mao et al (2005). Browne et al (2009) conducted impact tests of an MREA at stroking velocities ranging from 1.0 to 10 m/s and showed that the MR damper force could be tuned by adjusting the magnetic field.…”
Section: Introductionmentioning
confidence: 91%
“…A schematic diagram of annular duct type MR valve in a typical flow-mode MREA (or interchangeably called MR damper in this study) is presented in Figure 2. According to the BP nonlinear flow model, which considers laminar and turbulent flows (Franzini and Finnemore, 1997; Mao et al, 2005; White, 1986), the damping force, F , of the MR damper is given by…”
Section: Mrea (Mr Damper) Modelsmentioning
confidence: 99%
See 3 more Smart Citations